1997
DOI: 10.2214/ajr.169.6.9393197
|View full text |Cite
|
Sign up to set email alerts
|

Normal lower limb venous Doppler flow phasicity: is it cardiac or respiratory?

Abstract: The purposes of this study were to determine the origin and nature of normal lower limb venous Doppler flow phasicity and to assess normal and respiratory variations. SUBJECTS AND METHODS. The common femoral veins of 12 healthy volunteers (three men and nine women; age range. 21-50 years; mean. 29 years) were evaluated by detailed spectral Doppler examinations with simultaneous ECG and respirometric tracings. The examinations were performed using a 5-or 7-MHz linear-array transducer with breath held in mid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 3 publications
3
38
0
Order By: Relevance
“…Additionally, the duration of the examination, 1.5 h, may not have been sufficient to observe leg swelling and edema, a problem when traveling for ‡2 h with the risk rising exponentially with increasing time of travel [21]. Blood flow in the popliteal vein varies between individuals and differs in a single person [25] over time because of body position, breathing and the cardiac cycle [26]; therefore, reproducibility of velocity results will not be precise [17]. Reports have shown that a coefficient of variation of <20% is acceptable [27].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the duration of the examination, 1.5 h, may not have been sufficient to observe leg swelling and edema, a problem when traveling for ‡2 h with the risk rising exponentially with increasing time of travel [21]. Blood flow in the popliteal vein varies between individuals and differs in a single person [25] over time because of body position, breathing and the cardiac cycle [26]; therefore, reproducibility of velocity results will not be precise [17]. Reports have shown that a coefficient of variation of <20% is acceptable [27].…”
Section: Discussionmentioning
confidence: 99%
“…24 The pattern of flow will change according to the particular physiology and body position at the time, with breathing and the cardiac cycle modulating the flow to differing extents. 25 Moreover, venous blood pressure will change; therefore, the reproducibility of the velocity results from a particular pump in a particular individual over time will not be perfect.…”
Section: What Effect Do Intermittent Compression Systems Have On Venomentioning
confidence: 99%
“…Eight of the 13 abnormal VUS findings described in the literature were detected. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Abnormal VUS waveforms were found in 84 patients (45.9%), 54 (40.6%) of whom were in group I and 30 (60%) of whom were in group II. Within group I, there was a larger number of abnormal findings among patients for whom tests for a range of different pathologies had already been requested (63.6%) than among those patients who had been invited to take part at the clinic (36.36%).…”
Section: Resultsmentioning
confidence: 99%
“…The following cardiac-induced changes to peripheral VUS waveforms are described in the literature: arrhythmia 2,6,7 ( Figures 1, 2 and 3), pulsatile waves in the common femoral and popliteal veins 2,8 (Figure 4), systolic pulsus bisferiens 6,[9][10][11] (Figures 3 and 5), low peak systolic velocity, 1 bradycardia 2 ( Figure 5), tachycardia, 2 pulsus alternans, 12 pulsus tardus et parvus, [11][12][13] water hammer pulse, 9 systolic spike and dome, 13 elevated peak systolic velocity caused by high cardiac output, 10 pulsus paradoxus, 14 and waves caused by cardiac assistance devices. 11,12,15 The objectives of this study were to evaluate the presence of these spectral changes in VUS waveforms from elderly patients who underwent vascular arterial and/or venous echography and to analyze the degree of agreement between these findings and cardiological examinations and diagnoses.…”
Section: 4mentioning
confidence: 98%